Menakar Teks, Menyemai Makna: Pelatihan Teknik Raygor untuk Guru - Hambali, Muhammad; Setiawati, M.Pd, Dr. Eti; Warsiman (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
The quality of text readability is very necessary for teachers to choose teaching materials that suit learning needs. However, quite a few teachers do not know the readability level of the text which should be the basis for selecting books, thus having an impact on students' ability to grasp the content and learning material being taught. The aim of this community service is to provide training on the readability level of textbooks to teachers at the Al-Ma'arif Nahdhatul Ulama Foundation, Dau sub-district, Malang district. The expected benefit is that teachers at the Al-Ma'arif Nahdhatul Ulama Foundation, Dau sub-district, Malang district, understand more deeply about the readability of textbooks used in learning. The activities carried out were providing training followed by discussions and questions and answers about the material. The results of community service concluded that the teachers at the Al-Ma'arif Nadhatul Ulama Foundation, Dau subdistrict, Malang district, after receiving training on textbook readability, had a good understanding of the readability of textbooks as learning materials in the classroom. Therefore, this training is very useful for teachers in preparing good teaching materials for students.